Liberating judgment : fanatics, skeptics, and John Locke's politics of probability - Casson, Douglas (Princeton University Press, 2011)
Examining the social and political upheavals that characterized the collapse of public judgment in early modern Europe, Liberating Judgment offers a unique account of the achievement of liberal democracy and self-government. The book argues that the work of John Locke instills a civic judgment that avoids the excesses of corrosive skepticism and dogmatic fanaticism, which lead to either political acquiescence or irresolvable conflict.